Specific Inhibition of Elm1 Kinase Activity Reveals Functions Required for Early G(1) Events - Sreenivasan, Aparna (American Society for Microbiology, 2003)
In budding yeast, the Elm1 kinase is required for coordination of cell growth and cell division at G(2)/M. Elm1 is also required for efficient cytokinesis and for regulation of Swe1, the budding yeast homolog of the Wee1 kinase. To further characterize Elm1 function, we engineered an ELM1 allele that can be rapidly and selectively inhibited in vivo. We found that inhibition of Elm1 kinase activity during G(2) results in a phenotype similar to the phenotype caused by deletion of the ELM1 gene, as expected. However, inhibition of Elm1 kinase activity earlier in the cell cycle results in a prolonged G(1) delay. The G(1) requirement for Elm1 kinase activity occurs before bud emergence, polarization of the septins, and synthesis of G(1) cyclins. Inhibition of Elm1 kinase activity during early G(1) also causes defects in the organization of septins, and inhibition of Elm1 kinase activity in a strain lacking the redundant G(1) cyclins CLN1 and CLN2 is lethal. These results demonstrate that the Elm1 kinase plays an important role in G(1) events required for bud emergence and septin organization.